1997
DOI: 10.1359/jbmr.1997.12.12.2076
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Influences on Muscle Strength, Lean Body Mass, and Bone Mineral Density: A Twin Study

Abstract: Lean body mass and muscle strength are both associated with bone mineral density (BMD), which is known to be under strong genetic control. In this classical twin study, we examine the size of the genetic component of both muscle strength and lean body mass and to what degree they account for the genetic component of BMD. In all, 706 postmenopausal women were examined; 227 pairs of monozygous (MZ) twins and 126 pairs of dizygous (DZ) twins. Grip strength was measured using a hand-help grip bulb and leg strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
223
3
4

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 375 publications
(237 citation statements)
references
References 27 publications
7
223
3
4
Order By: Relevance
“…In the study of 353 postmenopausal female twin pairs, Arden and Spector [1997] found a grip strength heritability of 30%. The two twin studies on grip strength among men represented 257 male twin pairs aged 59-69 at baseline [Reed et al, 1991] and a 10-year follow-up on 152 of these pairs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of 353 postmenopausal female twin pairs, Arden and Spector [1997] found a grip strength heritability of 30%. The two twin studies on grip strength among men represented 257 male twin pairs aged 59-69 at baseline [Reed et al, 1991] and a 10-year follow-up on 152 of these pairs .…”
Section: Discussionmentioning
confidence: 99%
“…Three previous papers based on two populations addressed the issue of grip strength heritability, using either solely men [Reed et al, 1991; or solely women [Arden and Spector, 1997], and in smaller samples than in this study. In the study of 353 postmenopausal female twin pairs, Arden and Spector [1997] found a grip strength heritability of 30%.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic effects accounted for 52-84% of the variation in LBM among older female twins, i.e. women averaging 45 years (Seeman et al 1996) or~53 years of age (Nguyen et al 1998) and premenopausal women (Arden and Spector 1997). In a study by Schousboe et al, the heritability of LBM was 61% among female twins aged 18-67 years (Schousboe et al 2004).…”
Section: Heritability Studiesmentioning
confidence: 98%
“…The heritability of a given phenotype can be analysed in twin studies. Published research with older twins has reported that heritability can explain 22% to 52% of the variance in muscle strength, the latter been typically assessed with handgrip dynamometry (Arden and Spector 1997;Carmelli and Reed 2000;Frederiksen et al 2002;Reed et al 1991). The relative contribution of genetic and environmental effects to the individual variability in muscle strength changes over the ageing process.…”
Section: Heritability Studiesmentioning
confidence: 99%
“…As displayed in figures of postflight BMD changes, some crew members recover within the first year after return while others do not recover until much later. Factors that contribute to this variability in recovery are likely to include nutrition [15,16], skeletal muscle reconditioning [17], and genetics [18,19]; some of these factors may delay the ability and motivation of crew members to become ambulatory and thus mechanically load their skeletons. It is interesting to note that two of the three outliers for BMD loss in the proximal femur (greater than a 15% deficit in femoral neck and trochanter) were older than the average age of, or in space longer than the average duration for, long-duration crew members; the missions corresponding to these outliers also represented their first long-duration flight.…”
Section: Introductionmentioning
confidence: 99%